DISPARITAS PENJATUHAN PIDANA TAMBAHAN DALAM PERKARA TINDAK PIDANA KORUPSI PENGADAAN BARANG DAN JASA (Studi kasus putusan PN Mamuju Nomor: 3/ Pid-Sus-TPK/2021/PN. Mam. dan putusan PN Bandung Nomor: 55/ Pid-Sus-TPK/2021/PN. Bdg) - Hans Poliman; Ade Adhari (Jurnal Hukum Adigama, 2021)
Indonesia is one of the countries that guarantees justice for everyone. In practice, justice and legal certainty as laid out in the foundation of our country is only a sweet writing that has not been properly applied." One of the injustices that are often experienced by the people who find justice (Justiciabelen) especially in the field of justice is the disparity of prosecution. Basically, the disparity of prosecution is something that is natural because the fact of the trial in one case against another case certainly has a uniqueness even though it is ensnared with the same article of laws and regulations. But a verdict can be categorized as disparity if it is not accompanied by clear or erroneous considerations in understanding the formulation of the article indicted so as to cause injustice and can cause suspicions in the community. One of the criminal acts that often experience disparity of prosecution is the crime of corruption. This can be compared to 2 (two) verdicts, namely the Decision of PN Mamuju Number: 3 / Pid-Sus-TPK / 2021 / PN. Mam. and Decision of PN Bandung Number: Number: 55Pid.Sus-TPK/2020/PN Bdg on behalf of Shokhibul Hidayat. Where the Panel of Judges who tried Defendant Saddam Maulana Arief, ST and Defendant Shokhibul Hidayat have different considerations. Thisattracted researchers to conduct an analysis of THE Verdict of PN Mamuju Number: 3 / Pid-Sus-TPK / 2021 / PN. Mam is seen from the disparity category. Based on the results of aanalysis conducted by PN Mamuju Decision Number: 3 / Pid-Sus-TPK / 2021 / PN. Mam has fulfilled the category of disparity in imposing additional charges on defendants because it is wrong in formulating the Corruption Eradication Act.